Dimension‐Matched Zinc Phthalocyanine/BiVO4 Ultrathin Nanocomposites for CO2 Reduction as Efficient Wide‐Visible‐Light‐Driven Photocatalysts via a Cascade Charge Transfer. Issue 32 (19th July 2019) - Bian, Ji; Feng, Jiannan; Zhang, Ziqing; Li, Zhijun; Zhang, Yuhang; Liu, Yadi; Ali, Sharafat; Qu, Yang; Bai, Linlu; Xie, Jijia; Tang, Dongyan; Li, Xin; et al.
Abstract: Cascade charge transfer was realized by a H‐bond linked zinc phthalocyanine/BiVO4 nanosheet (ZnPc/BVNS) composite, which subsequently works as an efficient wide‐visible‐light‐driven photocatalyst for converting CO2 into CO and CH4, as shown by product analysis and 13 C isotopic measurement. The optimized ZnPc/BVNS nanocomposite exhibits a ca. 16‐fold enhancement in the quantum efficiency compared with the reported BiVO4 nanoparticles at the excitation of 520 nm with an assistance of 660 nm photons. Experimental and theoretical results show the exceptional activities are attributed to the rapid charge separation by a cascade Z‐scheme charge transfer mechanism formed by the dimension‐matched ultrathin (ca. 8 nm) heterojunction nanostructure. The central Zn 2+ in ZnPc could accept the excited electrons from the ligand and then provide a catalytic function for CO2 reduction. This Z‐scheme is also feasible for other MPc, such as FePc and CoPc, together with BVNS. Abstract : Dimension‐matched zinc phthalocyanine/BiVO4 nanosheet (ZnPc/BVNS) nanocomposites were developed as efficient visible‐light‐driven photocatalysts for converting CO2 into CO and CH4 . Exceptional activities are attributed to the rapid charge separation by a cascade Z‐scheme charge transfer mechanism formed by the dimension‐matched ultrathin (ca. 8 nm) heterojunction nanostructure.